A high fat diet does not affect the iron bioavailability in Wistar rats fed with chia and increases gene expression of iron metabolism proteins - Silva, Bárbara Pereira da; Matyelka, Jéssika Camila da Silva; Moreira, Maria Eliza de Castro; Toledo, Renata Celi Lopes; Lucia, Ceres Mattos Della; Pinheiro-Sant'Ana, Helena Maria; Martino, Hércia Stampini Duarte (Food & Function, 2016)
This study evaluated the effect of chia on the iron bioavailability and gene expression of proteins involved in iron metabolism in animals fed with a high fat diet and a standard diet. Four experimental groups were tested (n = 8): standard diet + ferrous sulfate (SD + FS), standard diet + chia (SD + C), high fat diet + ferrous sulfate (HFD + FS), high fat diet + chia (HFD + C). The hemoglobin gain, hemoglobin regeneration efficiency, biological relative value of HRE, serum ferritin and transferrin, liver iron concentration and gene expression of proteins were evaluated. The SD + C group showed lower transferrin expression when compared to the control group. The control group showed serum transferrin concentration higher than the other groups. Serum ferritin and liver iron concentration did not differ among the animals that received chia ferritin and hephaestin expression was lower in experimental groups when compared with the control group. The peroxisome proliferator activated receptor expression was higher in animals fed with SD + C than in the control group. The expression of duodenal cytochrome B and divalent metal transporter 1 in the HFD + C group was higher and ferroportin was lower in the groups containing chia. Animals fed with chia showed similar iron bioavailability compared to animals fed with ferrous sulfate.
Keywords: High fat diet; Iron bioavailability; Metabolism proteins